PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Faridhatun Faidah; Dian Wismar’ein (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2021)
The purpose of this research is to test the profitability condition of a company on the stock price by using the capital structure as a mediating variable. This study is to take a sample of the property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period, which obtained 21 companies using purposive sampling technique. This study uses path analysis. The test results found that there is a significant negative effect between profitability on capital structure. Profitability and capital structure also have a significant positive effect on stock prices. In addition, the capital structure has also been shown to significantly mediate the effect of profitability on share prices